Relevansi Ilmu Pengetahuan Sosial dalam Mengembangkan Kecakapan Abad 21 - Esti Wuryani; Tarto Tarto (UM Purwokerto Press, 2022)
Social studies education must accommodate 21st century learning so that social studies learning becomes more meaningful and meaningful in the midst of advances in information and communication technology. This study aims to describe and analyze the relevance of social studies learning to life skills in the 21st century. The research findings reveal that the relevance of social studies learning to 21st century skills is already evident in the basic competencies to be achieved. However, if social studies learning is presented conventionally, social studies learning will lose its meaning. Therefore, social studies learning must apply learning designs that condition students to think critically, creatively, communicate, and collaborate, including project based learning, problem based learning and cooperative learning.